2019
DOI: 10.1093/mmy/myz104
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors predicting Candida infective endocarditis in patients with candidemia

Abstract: Abstract Candida infective endocarditis (CIE) is a rare but serious complication of candidemia. Incidence and risk factors associated with CIE among candidemic patients are poorly defined from small cohorts. Identification of clinical predictors associated with this entity may guide more judicious use of cardiac imaging. We conducted a retrospective analysis of all inpatients aged ≥18 years diagnosed with candidemia at our institution. CIE was diagnosed by fulfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
1
17
0
1
Order By: Relevance
“…Two (10%) additional cases involved infected CIED wires. An analysis of the risk of CIE in patients with candidaemia identified valvular heart disease as the most common exposure, with a sevenfold increased risk of CIE when these patients have candidaemia 22 . This was similar to our cohort with 10 (77%) of the IDU patients having history of previous IE.…”
Section: Discussionsupporting
confidence: 86%
“…Two (10%) additional cases involved infected CIED wires. An analysis of the risk of CIE in patients with candidaemia identified valvular heart disease as the most common exposure, with a sevenfold increased risk of CIE when these patients have candidaemia 22 . This was similar to our cohort with 10 (77%) of the IDU patients having history of previous IE.…”
Section: Discussionsupporting
confidence: 86%
“…A recent retrospective cohort study evaluating risk factors for CIE among patients with candidemia showed a similar pattern. Although valvular heart disease was associated with a higher odds of CIE (OR, 7.66; 95% CI, 3.0–19.8), both hematologic malignancy and receipt of TPN were associated with a lower odds of CIE [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A baseline assessment of the risk of having therapeutic failure may help clinicians to advance difference strategies depending on the baseline BDG value. The routine screening of deep‐seated infections in candidemia that is mentioned in most guidelines, such as dilated fundoscopy to diagnose endophthalmitis and echocardiography to diagnose endocarditis, increases hospitalisation costs and has been argued by some authors, due to the low prevalence of such complications in most series 32,33 . In this perspective, we explored the possibility of using baseline BDG as a reference for selecting patients where imaging and eye examination for screening deep‐seated infections should be performed.…”
Section: Discussionmentioning
confidence: 99%